THE INFLUENCE OF EXPORT PRODUCT PRICE, TOTAL PRODUCTION, AND DISTRIBUTION COST ON THE EXPORT VOLUME OF RK95-1-NB (A CASE STUDY OF DIESEL ENGINE MANUFACTURER IN PT KUBOTA INDONESIA) - Nidia - Yuniar; Riyadi - Riyadi; Lusia M Silitonga (Politeknik Negeri Semarang, 2017)
The purposes of this research are to analyze the influence of export product price, total production, and distribution cost on export volume of RK95-1-NB Diesel Engine simultaneously and partially and to find out how many contribution of each variable. The variables mentioned in this research are export product price, total production, and distribution cost as the independent variable and export volume as the dependent variable. This research uses secondary data in the form of time series data annually starting from 2010 to 2016. The analysis methods in this research are classic assumption test (which are includes normality test, heterocedasticity test, multicollinearity test, and linearity test), T test, F test, and coefficient determination (R2). The result of structural equation is Export Volume=0,602 Export Product Price+0,402 Total Production+0,299 Distribution Cost. There is a partial influence among export product price and total production toward export volume. There is no partial influence between the distribution cost variables on export volume. The result of F test shows that there is a simultaneous influence among export product price, total production, and distribution cost on export volume RK95-1-NB Diesel Engine. The coefficient determination value (Adjusted R2 value) of the model is 0.943 (94.3%). It means that the contribution of export product price, total production, and distribution cost give contributions toward export volume RK95-1- NB diesel engine is 94.3% and the rest 5.7% is affected by other variables that are not described in this research.